Answer:
Step-by-step explanation:
Let x represent Mr Y's current age.
Let y represent the age of his daughter.
Mr. Y is 3 times as old as his daughter. This means that
x = 3y
In 15 years time, the sum of their age is 86. This means that
(x + 15) + (y + 15) = 86
x + y + 30 = 86 - - - - - - - - - -1
Substituting x = 3y into equation 1, it becomes
3y + y + 30 = 86
4y + 30 = 86
4y = 86 - 30 = 56
y = 56/4 = 14
x = 3y = 3 × 14 = 42
Mr Y is 42 years now
His daughter is 14 years now
When his daughter was born, Mr Y was 42 - 14 = 28 years